PENGARUH TERAPI MENULIS PENGALAMAN EMOSIONAL TERHADAP TINGKAT DEPRESI LANSIA DI PANTI WREDA DARMA BAKTI KASIH SURAKARTA - Tunjung Sri Yulianti; Ria Kurniawati (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Background : a person in the elderly will experience a failure to maintain a balance ofphysiological stress conditions, resulting in increased susceptibility to depression.Socioeconomic changes and social values of society, family system shift from extendedfamily to nuclear family, industrialization culture with independent character andindividualist consider elderly as "trouble maker" and become burden. This results in thetendency of the elderly to be excluded and, not getting treatment, so many choose toplace it in elderly homes. This condition will of course affect the incidence of depressionin the elderly. To overcome depression can be done various therapies, one of which iswriting therapy, the therapy that does not give priority to physical complaints but theenlightenment of the soul through the release of emotions. Expressive writing is a form ofwriting to release and explore the deepest traumatic emotions and thoughts that makethe sufferer feel an inner wound. Purpose of the study: to determine the effect of writingtherapy emotional experiences on the level of depression in the elderly.Methods : quasy experimental research. Data analysis using t test formula with SPSSprogram series 18. Subjects : elderly living in a nursing home.Results: the significance value of t test (2 tailed) is 0.015.Conclusion : that writing therapy can reduce the level of depression in the elderly.Keywords: Writing Therapy, Elderly Depression